The effect of uncertainty on foreign direct investment: The case of Mexico - Gabriela López Noria; Juan José Zamudio Fernández (Banco de México, 2018)
This paper investigates the effect of uncertainty on FDI flows into the Mexican manufacturing sector during the period 2007-2015. Using a panel of manufacturing subsectors, we estimate a model by System GMM that includes domestic and external factors, as well as idiosyncratic (i.e. that affect manufacturing subsectors in a particular way) and aggregate (i.e. that affect all manufacturing subsectors in general) uncertainty measures as explicative variables. We also perform some simulations to quantify the effect of uncertainty on FDI flows. The main results show that uncertainty discourages FDI flows into the Mexican manufacturing sector. We also find that the idiosyncratic uncertainty measures are more important in explaining FDI flows than the aggregate uncertainty measures, with the exception of the global risk aversion index.
Keywords: D80; F21; D84; L60; 330; Uncertainty; Foreign Direct Investment; Expectations; Manufacturing